Retrospection and Reference: The Early Spread of Marxism in Chinese Universities in the Early 20th Century: -- Taking the Teacher Group as an Example - Xie, Yingqi (Transactions on Social Science, Education and Humanities Research, 2024)
At the beginning of the 20th century, universities were an important battlefield for the dissemination of early Marxism, and teachers, as members of intellectuals, played an important role in the early dissemination of Marxism in China. This article, from the perspective of the teacher community, traces and analyzes the background, group characteristics, channels, content, and effects of the early dissemination of Marxism by the teacher community. Taking history as a lesson, it explores the benefits of expanding dissemination channels and methods in combination with the characteristics of the times, strengthening the construction of ideological and political theory courses in universities, and promoting the popularization of Marxism.